Financial Analysis with Microsoft Excel - Timothy R. Mayes (South-Western , Cengage Learning, 2007)
Now readers can master their Excel 2010 skills while establishing a strong understanding of contemporary corporate finance. Mayes/Shank's FINANCIAL ANALYSIS WITH MICROSOFT EXCEL 2010, 6E shows today's reader how to tap into some of Excel 2010's most powerful tools to solve real financial problems. The book's solid content addresses today's most important corporate finance topics, including financial statements, budgets, the Market Security Line, pro forma statements, cost of capital, equities, and debt. This edition now covers Excel tables, pivot tables and pivot charts and other areas that have become increasingly important to today's employers. The book's reader-friendly, self-directed learning approach and numerous study tools help readers build upon basic skills for the Excel 2010 proficiency and the solid finance knowledge business professionals need for success.